(untitled) (Annals of Medical Research, 2021)
Aim: To determine the bacterial prevalence and its susceptibility to antibiotics, and additionally, to investigate the relationship between bacterial status and recurrence and complications with regard to whether bacteria reproduce in the cyst cavity in uninfected pilonidal cyst. Material and Methods: The cases included in the study were those who applied to our clinic due to pilonidal sinus and surgical operation was decided. Before the operation, culture specimen was taken using a sterile swab stick from the cyst hole. The cyst was excised with a safety margin. The excised material was opened under the guidance of the cyst hole and the cavity was entered and samples of cyst tissue and content were collected for culture-antibiogram. Results: Totally 46 cases were included in our study, Average age was 26 (18-47) years. Limberg flap was performed to 37 (78%) of the cases, and primary repair to 9 (22%) cases. Average follow-up period was 27.1 (sd±7.6) months. Normal bacterial skin flora was determined in 6 (13%) cases and significant bacterial reproduction in 4 (8.6%) cases (Enterococcus faecalis, Streptococcus anginosus, MRSA, Streptococcus dysgalactiae ) in the cyst cavity culture. In tissue culture however, skin bacterial flora was observed in 9 (19.5%) cases, while bacterial growth only in 1 case. Recurrence was determined in 3 (3.6%) cases in total. Bacterial growth, and other factors were not associated with recurrence (p> 0.05)Conclusion: In this study, non-infected pilonidal sinus surgery does not require bacterial culture to prevent recurrence.Keywords: Pilonidal sinus; recurrence; surgery; culture.